Some abuse of foods - Cottrell, Sarah Esther (My University, 1894)
Introduction: The one essential to all life is nourishment. Nowhere can life exist unless it requires nourishment from some source. It may be obtained directly or indirectly but food must be had in some form or else there will be premature death and then decay. We generally consider anything as a food if it builds up the tissues of the body, contributes to the process of nutrition, supplies us with nervous force and energy and enables us to accomplish all things that are in reach of human power. We do not live upon what we eat but upon what we digest and to judge accurately of the nutritive value of foods we must know how much of each is assimilated. We cannot draw the live anywhere as to the value of foods, “for what agrees with one man may be another man’s poison”; that will supply the body with ample nourishment in certain occupations and at certain periods of life wil only be starvation measures under different circumstances.
Citation: Cottrell, Sarah Esther. Some abuse of foods. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Food; Nourishment; Diet; Dietary; Health; Theses; Manuscripts (documents)